Severe soft tissue ossification in a southern right whale Eubalaena australis - la Sala, Luciano Francisco (2012)
The carcass of a stranded southern right whale Eubalaena australis, discovered on the coast of Golfo Nuevo in Península Valdés, Argentina, exhibited extensive orthotopic and heterotopic ossification, osteochondroma-like lesions, and early degenerative joint disease. Extensive soft tissue ossification led to ankylosis of the axial skeleton in a pattern that, in many respects, appeared more similar to a disabling human genetic disorder, fibrodysplasia ossificans progressiva (FOP), than to more common skeletal system diseases in cetaceans and other species. This is the first reported case of a FOP-like condition in a marine mammal and raises important questions about conserved mechanisms of orthotopic and heterotopic ossification in this clade.